Pengaruh Stakeholder Pressure, Ukuran Perusahaan dan Kinerja Keuangan terhadap Sustainability Reporting Disclosure - Syakira, Nadiya; Chandra, Novrina; Mustika, Rasyidah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The aim of this research is to determine the influence of employee pressure, foreign ownership, management ownership, financial performance, and company size on Sustainability Reporting Disclosure in environmentally sensitive companies. The independent variables used in this study are employee pressure, foreign ownership, management ownership, Return on Assets (ROA), and the logarithm of total assets. The dependent variable, Sustainability Reporting Disclosure, is measured according to the Global Reporting Initiative (GRI) reporting guideline with 79 indicator items. This research employs a quantitative approach. The research population includes companies categorized as environmentally sensitive and listed on the Indonesia Stock Exchange (IDX) that have published Sustainability Reports during the research period from 2019 to 2021. The data collection technique used purposive sampling, in which the sample was based on predefined criteria. The sample consists of 46 companies with 138 observations. Data analysis was conducted using multiple linear regression technique using IBM SPSS Statistics 25 software. The research findings reveal that the foreign ownership and company size variables have a significant influence on Sustainability Reporting Disclosure, while employee pressure, management ownership, and financial performance variables do not exhibit any significant influence.